2017
DOI: 10.1080/09553002.2018.1399226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radioadaptive response and individual radiosensitivity to low doses of gamma radiation: an extended study of chromosome damage in blood lymphocytes of three donors

Abstract: AR variability in human lymphocytes is not attributed to variation in radiosensitivity among individuals and is more drastic than was believed. It seems doubtful that AR is a universal phenomenon which has a consistent impact on the effects of radiation exposure on humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Besides, ALA can restore the reduced/oxidized glutathione ratio (GSH/GSSG) by either transferring electrons directly to the GSSG for reduction or increasing the synthesis of GSH through improving the plasma uptake of cystine to subsequently reduce it to cysteine, which is the precursor of glutathione. 54 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, ALA can restore the reduced/oxidized glutathione ratio (GSH/GSSG) by either transferring electrons directly to the GSSG for reduction or increasing the synthesis of GSH through improving the plasma uptake of cystine to subsequently reduce it to cysteine, which is the precursor of glutathione. 54 …”
Section: Discussionmentioning
confidence: 99%
“…52 Concerning the radio adaptive effect of LD radiation, the obtained results are in agreement with previous studies 23,53 ; the latter indicated that exposure of rats to whole-body LD radiation (.5 Gy as a single dose or 2 fractions) restored GSH and reduced MDA to a significant levels and afforded hepatoprotection and neuroprotection against paracetamol and thioacetamide-induced acute liver damage and hepatic encephalopathy. This effect may be due to simultaneous stimulation of many independent cellular functions as an antioxidant defense mechanism and DNA repair mechanisms through regulation of some gene networks in response to DNA damage (Komova et al 2018) inducing more radio resistance to a subsequent HD. 54 Previously, Radwan et al (2012) explained that the LD of radiation might enhance free radical formation with the concomitant enhancement of the antioxidant mechanisms that overwhelmed the formed free radicals and finally predominated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are no other specific studies indicating the presence of an AR in patients exposed to ionizing radiation for medical reasons. Some studies on AR in humans have only been performed ex vivo on lymphocytes taken from healthy donors [ 10 ] or refer to cohorts of healthy donors from occupational or environmental exposures [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%